KONSEKUENSI YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 13/PUU-XV/2017 TERHADAP TENAGA KERJA YANG MEMILIKI IKATAN PERKAWINAN DENGAN SESAMA TENAGA KERJA DALAM SATU PERUSAHAAN - Trisnadiasa, I Nyoman Agus; Tagel, Dewa Putu (Institut Hindu Dharma Negeri Denpasar, 2019)
The Problems that emerged in a marriage in Indonesia, visible seen in arrangement marriage in tje workplace, each worker / laborers in one company will undertake ongoing marriage, some companies both by the governmenr, and private, establishes a clause that limits the right to undertake ongoing marriage between workers/laborers in one company. That the existence of a clause the termination of employment, so that constitutional court thought the regulation contraty contrary constitutional the art 28D paragraph 1 the contitution of 1945 that everyone is entitled to form family and to survive through marriage legitimate. Expected forcompany follow the constitutional court decisions.